Pelaksanaan Gerakan Masyarakat Maghrib (GEMMAR) Mengaji dan Implikasinya terhadap Karakter Religius Remaja di Kabupaten Kudus - Khomsatun (Lembaga Yasin AlSys, 2026)
The Gerakan Masyarakat Maghrib Mengaji (Gemmar Mengaji) is a religious program aimed at revitalizing the tradition of reciting the Qur’an after the Maghrib prayer while strengthening the religious character of the community, particularly adolescents. This study aimed to analyze the implementation of the Gemmar Mengaji Program, examine its implications for the development of adolescents’ religious character, and identify the supporting and inhibiting factors in its implementation in Kalirejo Village, Undaan Subdistrict, Kudus Regency. The study employed a qualitative approach using field research. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña, which comprised data condensation, data display, and conclusion drawing. The results showed that the Gemmar Mengaji Program was implemented regularly through the habituation of congregational prayers, Qur’an recitation, the study of religious texts, and moral development. The implementation of the program had positive implications for the development of adolescents’ religious character, as indicated by increased discipline in worship, greater love for the Qur’an, improved religious understanding, and better social behavior. The success of the program was supported by the commitment of religious leaders, family participation, and the community’s religious culture, whereas the influence of digital technology, the low motivation of some adolescents, and limited family guidance constituted inhibiting factors. This study affirms that Gemmar Mengaji functions not only as a Qur’anic literacy program but also as a community-based model of religious character education that contributes to the development of a younger generation with noble character.